Remembering the War and Aggression: A Discourse Analysis of Japan’s State Apologies and Commemoration Speeches on August 15th 1995-2015 - Jämsä, Heli (fi=Turun yliopisto|en=University of Turku|, 2016)
Memories of historical injustices affect contemporary politics from local to global level. In East Asia, questions of commemoration and historical responsibility have turned into international and domestic controversies. The main focus has been and still is in apologies conducted by Japanese prime ministers in regards to the war, aggression and colonialism during the era of Imperial Japan. Although it is granted that state apologies are not a crucial part of reconciliation, they can be analysed as a linked but separate process within the context of memory and international relations. The purpose of this study is to examine the discourses of history in Japanese prime ministers’ commemoration speeches on Memorial Ceremony for the War Dead from 1995 to 2015 in order to analyse how the Japanese government is reflecting on its past. In particular, attention is paid on what is being commemorated and how, whether it is the war and its victims or Japan’s post-war era of peace. As an apology is a reciprocal activity, responses from Japan’s most vocal former victims, South Korea and China, were also examined. Discourse analysis was used to identify and examine the different representations of the past. In addition, the apology statements of Japanese prime ministers were analysed in the Many to Many apology framework developed by Tavuchis (1991). Primary material consisted of 21 prime ministers’ speeches from the annual Memorial Ceremony for the War Dead on August 15th and from three apology statements made in 1995, 2005 and 2015. Further international context was primarily collected from newspaper articles of The New York Times and The Times throughout the examined period. It can be concluded from the findings that in the official Japanese remembrance of the past war from 1985’s annexation of Taiwan to the atomic bombings in 1945, both discourses that reinforce apology and remorse over Japan’s past aggressions and discourses that consciously avoid doing so are used. The commemoration speeches and apology statements consistently assert that Japan has acknowledged its past and expresses regret over the acts of aggression. At the same time, the speeches and statements strengthen the narrative that Japan was a victim of circumstances as well as turn the focus on post-war peace-making or on Japan’s own victimhood.